Study on the Dynamic Problems of Double-Disk Rotor System Supported by Deep Groove Ball Bearing - Yang Liu; Jiyuan Han; Siyao Zhao; Qingyu Meng; Tuo Shi; Hui Ma (Shock and Vibration)
Aiming at the analysis of the dynamic characteristics of the rotor system supported by deep groove ball bearings, the dynamic model of the double-disk rotor system supported by deep groove ball bearings was established. In this paper, the nonlinear finite element method is used combined with the structural characteristics of deep groove ball bearings. Based on the nonlinear Hertz contact theory, the mechanical model of deep groove ball bearings is obtained. The excitation response results of the rotor system nodes are solved by using the Newmark-β numerical solution method combined with the Newton–Raphson iterative method. The vibration characteristics of the rotor system supported by deep groove ball bearings are studied deeply. In addition, the effect of varying compliance vibration (VC vibration) caused by the change in bearing support stiffness on the dynamics of the system is considered. The time domain and frequency domain characteristics of the rotor system at different speeds, as well as the influence of bearing clearance and bearing inner ring’s acceleration on the dynamics of the rotor system are analyzed. The research shows that the VC vibration of the bearing has a great influence on the motion of the rotor system when the rotational speed is low. Moreover, reasonable control of bearing clearance can reduce the mutual impact between the bearing rolling element and the inner or outer rings of the bearing and reduce the influence of unstable bearing motion on the vibration characteristics of the rotor system. The results can provide theoretical basis for the subsequent study of the nonlinear vibration characteristics of the deep groove ball bearing rotor system.